Improving Learning Activities Using Visual Media in Class III Elementary School - Khuzaimah Khuzaimah; Hadiyanto Hadiyanto; Risda Amini (Postgraduate School, Universitas Negeri Padang, 2021)
The main problem in this classroom action research is the low activity and learning outcomes of students in thematic learning, which is caused by the teacher's less optimal in delivering learning material during the learning process in the classroom. This can be seen from the results of the tests which identified the low average score of students' daily tests in each subject and through interviews. This research is a classroom action research (PTK). This research was conducted at Raudhatul Jannah Islamic Elementary School in the second semester of the 2014/2015 academic year. The research subjects were 24 grade III students. The data analysis in this study were quantitative and qualitative descriptions. This research was conducted in two cycles, namely the Environmental Theme with the sub-theme of My Home Environment. The results of the study were seen in the observation sheet of student and teacher activities in the learning activities of cycle I and cycle II in the good category. Meanwhile, based on the results of the first cycle test, the students completed individually as many as 16 out of 24 students. With 67% classical completeness. Whereas in cycle 2 students who completed individually were 22 out of 24 students with 92% classical completeness. It can be concluded that using visual media can increase the activity and thematic learning outcomes of students in grade 3.